1999
DOI: 10.1046/j.1464-410x.1999.00925.x
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the immunological environment based on intratumoral cytokine production in renal cell carcinoma

Abstract: Objective To assess the immunological relationship whom showed a higher level than the mean, and IL-6 was produced in 32 (91%) of whom 10 (29%) showed between tumour and host, focusing on the production of T-cell helper (Th) subset-derived cytokines in a higher level than the mean. IL-10 was detected in 28 patients (80%) of whom 14 (40%) showed a higher patients with renal cell carcinoma (RCC). Patients and methods The study comprised 35 patients level than the mean. The production of these cytokines was close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 30 publications
2
21
0
2
Order By: Relevance
“…Recent studies in the peripheral blood showed higher IL-6 and IL-IO levels in patients with RCC than in healthy control s (38), and a positive correlation between IL-6 and IL-l 0 plasma levels, tumor size, tumor progression and prognosis (4,26,(38)(39)(40)(41)(42) . In their study investigating IL-IO expression in human RCC, Uwatoko et al (37) reported a decreased incidence of metastasis in patients with IL-IO levels than in those without IL-IO, and no correlation between IL-I 0 expression and prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies in the peripheral blood showed higher IL-6 and IL-IO levels in patients with RCC than in healthy control s (38), and a positive correlation between IL-6 and IL-l 0 plasma levels, tumor size, tumor progression and prognosis (4,26,(38)(39)(40)(41)(42) . In their study investigating IL-IO expression in human RCC, Uwatoko et al (37) reported a decreased incidence of metastasis in patients with IL-IO levels than in those without IL-IO, and no correlation between IL-I 0 expression and prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…The diminished type-1 response in RCC patients is not limited to MAGE-6 -specific and EphA2-specific CD4 + T cells. Following polyclonal activation, Onishi et al (9) showed that the peripheral blood lymphocyte response changes from predominantly type 1 to type 2 with advancing stage of RCC.…”
Section: Discussionmentioning
confidence: 99%
“…They found IL-4, as well as other Th2 cytokines, was usually up-regulated in patients with different types of cancers, such as renal cell cancer, non-small lung cancer, prostate cancer, colon cancer, breast cancer and other types of tumors (15). Onishi et al even found the IL-4 amount at tumor site was associated with the stage and grade of renal cancer (16).…”
Section: The Paradox Of Il-4 In Tumor Immunitymentioning
confidence: 99%